2010
DOI: 10.1071/an09165
|View full text |Cite
|
Sign up to set email alerts
|

Selection for fertility traits in Brahmans increases heifer pregnancy rates from yearling mating

Abstract: The performance of heifers from a Brahman herd that was selected for fertility was compared with Brahman heifers sourced from commercial properties using three year-groups of heifers. Each year, conception rates from yearling mating were significantly higher in heifers from the selected herd (SEL) than in heifers sourced from commercial properties (COM), despite the average joining weight of the SEL heifers being lower each year. The pregnancy rate in SEL heifers was 24% higher (P = 0.008) in the first year, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Nevertheless, age at first calving is favorably genetically associated with heifer rebreeding [ 66 ]. Schatz et al [ 67 ] showed that selection for fertility increases pregnancy rates of heifers exposed to reproduction at yearling in tropical conditions. In order to achieve reproductive efficiency, it is key to find the proper balance between sexual precocity and weight gain selection [ 68 ].…”
Section: The Genetics Of Heifers Sexual Precocitymentioning
confidence: 99%
“…Nevertheless, age at first calving is favorably genetically associated with heifer rebreeding [ 66 ]. Schatz et al [ 67 ] showed that selection for fertility increases pregnancy rates of heifers exposed to reproduction at yearling in tropical conditions. In order to achieve reproductive efficiency, it is key to find the proper balance between sexual precocity and weight gain selection [ 68 ].…”
Section: The Genetics Of Heifers Sexual Precocitymentioning
confidence: 99%
“…An important, overarching limitation continues to be nutritional and other environmental constraints on genetic expression of selected traits. Nevertheless, selection-line experiments have demonstrated that significant improvement in reproduction rates is possible in Droughtmaster (Davis et al 1993) and Brahman (Schatz et al 2010) breeds, as has the practical experience of astute and well-informed producers such as Alf Collins (Anon 2019). Recently, the genetic bases for these outcomes have become much better understood through research conducted by the CRC for Beef Genetic Technologies, particularly on defining the degree of genetic control for component physiological traits that underpin overall reproductive performance.…”
Section: Challenges and Opportunities For Genetic Improvement Of Repr...mentioning
confidence: 99%
“…Genetic improvement programs for female fertility in beef cattle has been hindered by the difficulty of collecting accurate fertility-related phenotypes needed to improve the predictive ability of genomic selection models (Tiezzi and Maltecca 2011). Some nucleus herds (or research stations) are capable of collecting very detailed, accurate and sometimes expensive fertility phenotypes (Schatz et al 2010). However, the size from these nucleus herds tends to be relatively small and sample size affects the predictive power of genomic selection.…”
Section: Table 6 Genomic Correlations Estimated Between Cow and Bull Fertility Traits In Brahman Andmentioning
confidence: 99%